2007
DOI: 10.1183/09031936.00083406
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and development of asthma, allergy and infections in a birth cohort

Abstract: Few studies have addressed associations between traffic-related air pollution and respiratory disease in young children. The present authors assessed the development of asthmatic/allergic symptoms and respiratory infections during the first 4 yrs of life in a birth cohort study (n5,4,000).Outdoor concentrations of traffic-related air pollutants (nitrogen dioxide PM 2.5 , particles with a 50% cut-off aerodynamic diameter of 2.5 mm and soot) were assigned to birthplace home addresses with a land-use regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
373
5
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 507 publications
(405 citation statements)
references
References 43 publications
16
373
5
11
Order By: Relevance
“…Asthma diagnosis can be made using objective methods, such as spirometry, at school ages. Nevertheless, given other evidence, 12,40 it is conceivable that air pollutants also enhanced the propensity toward lower respiratory tract illness-related wheeze in the present population.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 65%
See 2 more Smart Citations
“…Asthma diagnosis can be made using objective methods, such as spirometry, at school ages. Nevertheless, given other evidence, 12,40 it is conceivable that air pollutants also enhanced the propensity toward lower respiratory tract illness-related wheeze in the present population.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 65%
“…These findings suggest that early-life exposures to traffic pollutants may affect asthma severity and development. This view is supported by studies [12][13][14][15][16][17][18] of preschool children that have found increased risk of incident asthma or wheeze or cough without a cold from long-term exposures to local trafficrelated air pollutants using GIS-based methods. A recent study 35 showed acute increases in wheeze occurrence with elevations in daily regional NO 2 and NO x levels in infants and children followed up during their first 3 years of life.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Hypertension and road traffic noise (Bluhm et al, 2007). Impaired respiratory health (Oosterlee et al, 1996;Schikowski et al, 2005;Bayer-Oglesby et al, 2006;Sunyer et al, 2006;Brauer et al, 2007;Morgenstern et al, 2007). Diminished lung function (Sekine et al, 2004;Hong et al, 2005;Kan et al, 2007;McCreanor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma prevalence (Arif and Shah, 2007;Brauer et al, 2007;Carbajal-Arroyo et al, 2007). Children's lung development (Gauderman et al, 2007) Respiratory symptoms (Gordian et al, 2006).…”
Section: Introductionmentioning
confidence: 99%